A Novel Retinal Ganglion Cell Promoter for Utility in AAV Vectors - Hanlon, Killian S.; Chadderton, Naomi; Palfi, Arpad; Blanco Fernandez, Alfonso; Humphries, Peter; Kenna, Paul F.; Millington-Ward, Sophia; Farrar, G. Jane (Frontiers in Neuroscience, 2017)
Significant advances in gene therapy have enabled exploration of therapies for inherited retinal disorders, many of which are in preclinical development or clinical evaluation. Gene therapy for retinal conditions has led the way in this growing field. The loss of retinal ganglion cells (RGCs) is a hallmark of a number of retinal disorders. As the field matures innovations that aid in refining therapies and optimising efficacy are in demand. Gene therapies under development for RGC-related disorders, when delivered with recombinant adeno associated vectors (AAV), have typically been expressed from ubiquitous promoter sequences. Here we describe how a novel promoter from the murine Nefh gene was selected to drive transgene expression in RGCs. The Nefh promoter, in an AAV2/2 vector, was shown to drive efficient and preferential EGFP expression in murine RGCs in vivo following intravitreal injection. In contrast, EGFP expression from a CMV promoter was observed not only in RGCs, but throughout the inner nuclear layer and in amacrine cells located within the ganglion cell layer (GCL). Of note, the Nefh promoter sequence is sufficiently compact to be readily accommodated in AAV vectors, where transgene size represents a significant constraint. Moreover, this promoter should in principle provide a more targeted and potentially safer alternative for RGC-directed gene therapies.